Original paperThe association between periprocedural factors and the late outcome of percutaneous stenting of lower extremity arteries. A retrospective cohort study - Grzelązka, Paweł; Koza, Klaudia; Trofimiuk, Adrianna; Suppan, Karol; Wasielewski, Marcin; Wiśniewska, Joanna; Budzyński, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction: About 20–30% of the population have peripheral artery disease. Many of them require intervention, with a percutaneous procedure currently being the first choice. However, the outcomes of these interventions need regular evaluation due to continuous progress in endovascular techniques and the devices used. Aim: The aim of this study was to analyze procedural factors influencing the outcome of endovascular intervention in patients stented for the first time due to lower extremity atherosclerosis. Material and methods: The medical documentation of 91 patients with at least 1 year of follow-up after stenting of a lower limb artery was retrospectively evaluated. Uni- and multivariate analyses were performed. Results: The mean observation time was 544.4 ±502.9 days. The primary patency of a stent after such a follow-up was 68.1%. Cox proportional hazard analysis revealed that the risk of target lesion revascularization was affected by the following (hazard risk, 95% confidence interval): the number of vascular segments with significant lesions (13.14, 2.28–75.8); critical limb ischemia (5.68, 1.23–26.2); localization of the target lesion in an aorto-iliac in comparison with a femoro-popliteal vascular segment (0.37, 0.14–0.7); aorto-iliac lesion class according to the TASC-II consensus (1.96, 1.1–3.8); and claudication distance (1.02, 1.01–1.03). Conclusions: The common primary patency of a stent implanted into either an aorto-iliac or a femoro-popliteal vascular segment was similar to that found in other reports. The main factors affecting the outcome of the endovascular procedures performed were mainly related to atherosclerosis severity, not to the type of technique or device used.